Outiller l'enseignant pour soutenir une rétroaction centrée sur l'apprenant. Expérience d'introduction d'un outil de rétroaction lors de la production de schémas - Chantal Morin; Annie Carrier (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Producing conceptual maps is intended to support an active construction of knowledge by the student. To do so, feedback from the teacher is essential. However, few specific tools are available to support a truly student-centered feedback in conceptual mapping. This article provides a descriptive analysis of the perceived usefulness, from teachers’ perspective, of a short reflexive tool to optimized feedback to students. The reflexive tool was used with 99 first-year rehabilitation students. The tool consisted of two questions that each student had to complete and give to his/her tutor with the conceptual map produced following a problem-based session. Tutors (n = 11) clearly perceive the tool as useful in supporting written and verbal feedback to students regarding conceptual mapping. Specifically, the reflection tool gives structure to feedback, allows to focus on knowledge building and enables student-centered feedback instead of a content-centered one. In addition, the use of the reflexive tool did not increase time spent on feedback.